If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 0.5x + -5f(14) Multiply f * x fx = 0.5x + -5f(14) Reorder the terms for easier multiplication: fx = 0.5x + -5 * 14f Multiply -5 * 14 fx = 0.5x + -70f Reorder the terms: fx = -70f + 0.5x Solving fx = -70f + 0.5x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '70f' to each side of the equation. 70f + fx = -70f + 70f + 0.5x Combine like terms: -70f + 70f = 0 70f + fx = 0 + 0.5x 70f + fx = 0.5x Combine like terms: 0.5x + -0.5x = 0.0 70f + fx + -0.5x = 0.0 The solution to this equation could not be determined.
| 4x+9x-44=66-9x | | 10a-4b=10 | | -0.5x-2=7 | | -5x-5(2x-16)=155 | | 2(-4-5x)+6=2x-8 | | 6-(9-2)+3*6= | | -4x+20x=72 | | .8x+1.3=2x | | 172/-4+50-27=-20 | | 2(-4x-5)+6=2x-8 | | 9b^2-40=9+2b^2 | | 6x^2+53x-70=0 | | 38+7k=-8(k-4) | | 20=3z-4+9z | | f(x)=2x+5f(2) | | bc+x=xb+cx | | 2x+4=8-2x | | 3x-5(x+7)=-45 | | 3.4+10m=8.76 | | x^2-10x+18=20 | | 10t=-16t^2+12t+8 | | 6x+3(-3+10)=45 | | 6(36-10x)-8=-32 | | 4(f+2)+6=2(f-3)+5 | | 2x-5y+16z= | | 25x+2=1 | | 4x+3=24x-204 | | 4x+4(-4+10)=100 | | -4n+6(5n+4)=-14+7n | | 1+3y=10 | | 8(x-1)=2x-2 | | 8g+3=11 |